FE, MG AND AL DISTRIBUTION IN THE OCTAHEDRAL SHEET OF MONTMORILLONITES. AN INFRARED STUDY IN THE OH-BENDING REGION - Vantelon D.; Pelletier M.; Michot L.J.; Barres O.; Thomas F. (My University, 2001)
Ten montmorillonites of different origins with variable Fe contents were analysed using transmission IR spectroscopy. Special attention was devoted to the OH-bending region to obtain information about the distribution of octahedral cations. For low to medium Fe contents (≤0.56 per Si8 formula unit), a linear relationship between the position of the AlFeOH band and Fe content was observed. Such correlation might be explained by changes in the cis-trans occupancy of Fe in the octahedral sheet. Deconvolution of the OH-bending domain allows us to discriminate three components (δAlAlOH, δAlMgOH and δAlFeOH) which are correlated with cation abundances derived from chemical analysis. The relative area of each band can then be compared with theoretical areas calculated assuming a fully random distribution of cations in the octahedral sheet. Using such treatment, eight of the 10 montmorillonites studied presented a nearly randomized octahedral distribution. The two samples from Wyoming were clearly different as they exhibited a strong ordering tendency.
Keywords: montmorillonite; smectite; bentonite; IR spectroscopy; OH-bending region; octahedral cations